Plant species establishing beyond their introduced range are not always released from belowground enemies - Giancarlo M. Chiarenza; Angela T. Moles (Plant and Soil, 2025)
Background and aims Interactions with soil biota can shape the success of plants, but we still have much to learn about the role of belowground interactions in plant invasions. In this study, we investigated how soil factors affect the growth of an introduced plant species. Methods In a glasshouse experiment, we grew Plantago lanceolata L. seeds from Europe (native range) and Australia (introduced range) in soil samples collected from 21 sites within and beyond the established range of P. lanceolata in Australia. Results P. lanceolata seedlings grown in unsterilized soil were 34% smaller than seedlings grown in sterilized soil. The effect of soil biota on plant growth was not correlated with latitude or whether the soil was from the established range of P. lanceolata , just outside its range, or well beyond the species’ distribution. Individuals growing in new sites richer in organic carbon than their initial range experienced stronger release from belowground enemies. Conclusions Our study does not support the idea that plant species experience significant release from belowground enemy pressure when colonizing new regions. Rather, soil organisms have strong net negative impacts on plant growth regardless of soil origin.